Alterations in conflict monitoring are related to functional connectivity in Parkinson's disease. (September 2016) - Rosenberg-Katz, Keren; Maidan, Inbal; Jacob, Yael; Giladi, Nir; Mirelman, Anat; Hausdorff, Jeffrey M.
Abstract: Patients with Parkinson's disease (PD) have difficulties in executive functions including conflict monitoring. The neural mechanisms underlying these difficulties are not yet fully understood. In order to examine the neural mechanisms related to conflict monitoring in PD, we evaluated 35 patients with PD and 20 healthy older adults while they performed a word-color Stroop paradigm in the MRI. Specifically, we focused on changes between the groups in task-related functional connectivity using psycho-physiological interaction (PPI) analysis. The anterior cingulate cortex (ACC), which is a brain node previously associated with the Stroop paradigm, was selected as the seed region for this analysis. Patients with PD, as compared to healthy controls, had reduced task-related functional connectivity between the ACC and parietal regions including the precuneus and inferior parietal lobe. This was seen only in the incongruent Stroop condition. A higher level of connectivity between the ACC and precuneus was correlated with a lower error rate in the conflicting, incongruent Stroop condition in the healthy controls, but not in the patients with PD. Furthermore, the patients also had reduced functional connectivity between the ACC and the superior frontal gyrus which was present in both the incongruent and congruent task condition. The present findings shed light on brain mechanisms that are apparently associated with specific cognitive difficulties in patients with PD. Among patients with PD, impaired conflict monitoring processing within the ACC-based fronto-parietal network may contribute to difficulties under increased executive demands. Graphical abstract: When patients with Parkinson's disease (PD) were engaged in a word-color Stroop task they presented reduced connectivity within the ACC-based fronto-parietal attentional network. While reduced left ACC-parietal connectivity was selective to the conflict Stroop condition, left ACC-frontal connectivity was less specific, and was detected in the congruent condition as well. Lines represent functional connectivity in patients with Parkinson's disease as compared to healthy controls. ACC = anterior cingulate cortex; SFG = superior frontal gyrus.